2002
DOI: 10.1073/pnas.152121799
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a splice variant of DNA methyltransferase 3b, DNMT3b4, associated with DNA hypomethylation on pericentromeric satellite regions during human hepatocarcinogenesis

Abstract: DNA hypomethylation on pericentromeric satellite regions is an early and frequent event associated with heterochromatin instability during human hepatocarcinogenesis. A DNA methyltransferase, DNMT3b, is required for methylation on pericentromeric satellite regions during mouse development. To clarify the molecular mechanism underlying DNA hypomethylation on pericentromeric satellite regions during human hepatocarcinogenesis, we examined mutations of the DNMT3b gene and mRNA expression levels of splice variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
186
2
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(203 citation statements)
references
References 38 publications
14
186
2
1
Order By: Relevance
“…DNMT3B transcripts involving aberrant splicing events at the 5 0 end of the gene could be detected in all of the samples tested, except in HepG2 and Alexander cells, derived from hepatocellular carcinomas. Alexander cells are known to express DNMT3B4, which encodes a catalytically inactive DNMT3B isoform (Saito et al, 2002). All of the primary leukemia samples expressed a transcript containing aberrant splicing between exons 9 and 13 as originally observed, confirming that the expression of these novel mRNAs was not due to an artifact of in vitro culture.…”
Section: Cancer Cells Express Aberrant Dnmt3b Transcriptssupporting
confidence: 66%
See 2 more Smart Citations
“…DNMT3B transcripts involving aberrant splicing events at the 5 0 end of the gene could be detected in all of the samples tested, except in HepG2 and Alexander cells, derived from hepatocellular carcinomas. Alexander cells are known to express DNMT3B4, which encodes a catalytically inactive DNMT3B isoform (Saito et al, 2002). All of the primary leukemia samples expressed a transcript containing aberrant splicing between exons 9 and 13 as originally observed, confirming that the expression of these novel mRNAs was not due to an artifact of in vitro culture.…”
Section: Cancer Cells Express Aberrant Dnmt3b Transcriptssupporting
confidence: 66%
“…The only tumor type in which we did not observe novel DNMT3B transcripts was hepatocellular carcinoma. Interestingly, Alexander cells, derived from hepatocellular carcinomas, are known to express DNMT3B4, which encodes a catalytically inactive DNMT3B isoform (Saito et al, 2002). Furthermore, recently described transcripts from non-small-cell lung cancers, DDNMT3B5-7, are also predicted to encode truncated DNMT3B proteins lacking the catalytic domain (Wang et al, 2006a, b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that the epigenetic mechanism by which DNMT3B inactivates TSGs may be an important way in which TSGs are silenced in HCC. In HCC, the correlation between DNMTs' expression and the frequency of gene promoter methylation remains to be examined (Saito et al, 2002). In this study, we found that DNMT3B suppressed metastasis suppressor 1 (MTSS1) expression by directly binding to the promoter region of MTSS1, rather than DNA methylation.…”
Section: Introductionmentioning
confidence: 85%
“…Mouse studies have shown that both Dnmt3a and Dnmt3b are required for the establishment and maintenance of genomic methylation patterns and proper murine development (Bachman et al, 2001;Gowher and Jeltsch, 2002;Kaneda et al, 2004). DNMT3A and DNMT3B are upregulated in certain types of hematological malignancies and solid tumors, including leukocythemia (Mizuno et al, 2001;Claus and Lubbert, 2003), colorectal cancer Takeshima et al, 2006), lung cancer, breast cancer (Girault et al, 2003;Shafiei et al, 2008) and HCC (Saito et al, 2002;Choi et al, 2003). Specifically, DNMT3B contributes to oncogenic phenotypes (Linhart et al, 2007) and tumorigenesis in vivo by gene-specific de novo methylation and transcriptional silencing (Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%